Protection of air and groundwater in Polish municipalities of varying wealth as adaptation to climate change - Śmietanka, Tomasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Protection of air and groundwater as an adaptation to climate change is currently one of the main economic and social challenges at both the global, national, regional and local levels. This is confirmed by the autor`s review of the literature in this area. Higher wealth of Polish municipalities is not always consistent with greater municipal involvement in environmental protection and its results, which requires deeper analysis.
Keywords: climate changes; air protection; adaptation to climate change; zmiany klimatu; ochrona powietrza; adaptacja do zmian klimatu